Immune Response—With Particular Reference to the Use of Multiple Antigens - Wehrle, Paul F. (1968)
The increasing demand for preventive child health services and the general increase in international travel compel greater attention to the use of multiple antigens, both inactivated and live, when administered simultaneously. It appears that with the preparations currently licensed, multiple inactivated antigens may be given safely and with expectation of optimal effectiveness. dpt is a routine combination employed in combination with oral trivalent poliovaccine for primary immunization of infants and young children up to and including age six. Oral poliovirus vaccine and vaccinia may be administered at the time of the recall or booster dose of dpt vaccine during the second year of life, commonly at age 15 to 18 months. It is apparent from published data accumulated over many years that several antigens may be administered at the same time with adequate immunologic response. The minor differences in antibody response following simultaneous administration of live viral antigens is of unknown clinical importance. The primary reason for hesitancy in advocating greater use of multiple agents at this time is the theoretical consideration of possible neurotoxicity with those vaccines where the parent agent may have definite neurotoxicity. The question of possible additive or other harmful effects with measles, poliomyelitis, and rubella and mumps when given simultaneously can be answered only by carefully controlled studies involving close observation of the recipients with extension of these trials as data permit.